(untitled) (American Journal of Business Management, Economics and Banking, 2026)
In the financial system, public policy aimed at ensuring the sustainability of the national economy through the implementation of state programs at the national level is considered important, as is the process of financing this process and its financial oversight. The process of financial oversight of state programs also involves complex processes, the implementation of which requires the application of specific methodologies. Therefore, the scientific study of this process is a pressing issue. This article examines the methodological aspects of financial oversight and the implementation of state programs.